2015
DOI: 10.1080/15384047.2015.1016689
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial PAS domain-containing protein 1 confers TKI-resistance by mediating EGFR and MET pathways in non-small cell lung cancer cells

Abstract: Abbreviations: EGFR, epidermal growth factor receptor; NSCLC, non-small-cell lung cancer; TKIs, tyrosine kinase inhibitors; EPAS1, endothelial PAS domain-containing protein 1; HIF)-1a., hypoxia-inducible factorMutations in epidermal growth factor receptor (EGFR) rendering it constitutively active is one of the major causes for metastatic non-small-cell lung cancer (NSCLC), and EGFR-targeted therapies utilizing tyrosine kinase inhibitors (TKIs) are often used clinically as the first-line treatment. But approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…To the best of our knowledge, the only one that identified the upstream factor of EPAS1 in not only lung but also any type of human cancer. Interestingly, EPAS1 was also recently found to be responsible for the resistance of NSCLC to treatment by using tyrosine kinase inhibitors, which warrants further investigations to explore whether miR‐383 is also acting as an upstream factor of tyrosine kinase inhibitor‐resistant NSCLC, and whether this process is mediated by EPAS1 as well.…”
Section: Discussionmentioning
confidence: 98%
“…To the best of our knowledge, the only one that identified the upstream factor of EPAS1 in not only lung but also any type of human cancer. Interestingly, EPAS1 was also recently found to be responsible for the resistance of NSCLC to treatment by using tyrosine kinase inhibitors, which warrants further investigations to explore whether miR‐383 is also acting as an upstream factor of tyrosine kinase inhibitor‐resistant NSCLC, and whether this process is mediated by EPAS1 as well.…”
Section: Discussionmentioning
confidence: 98%
“…Sequencing of hub genes identified a new locus in EPAS1 that reached genome-wide significance and was validated in the largest lung cancer consortium, providing additional evidence that the HIFs-EGFR-HDAC4-TERT network is associated with NSCLC adenocarcinoma. Further, a recent study reported that EPAS1 could specifically bind to tyrosine kinase inhibitor (TKI)-resistant T790 M EGFR in NSCLC cell lines and enhance amplification of MET [ 46 ]. These findings suggest that EPAS1 is a key factor in EGFR-MET crosstalk in conferring TKI resistance in NSCLC cases and provide in vitro support of the HIFs-EGFR-HDAC4-TERT network.…”
Section: Discussionmentioning
confidence: 99%
“…Two HIF2α alleles, rs4953354 and rs13419896, were also shown to act as potential biomarker in lung cancer [32,33]. In a recent study, HIF2α also played important roles in tyrosine kinase inhibitor-resistant NSCLC cells [34].…”
Section: Discussionmentioning
confidence: 99%